Long-term fine particulate matter exposure and cardiovascular mortality in the general population: a nationwide cohort study. Issue 5 (May 2020) - Kim, In-Soo; Yang, Pil-Sung; Lee, Jinae; Yu, Hee Tae; Kim, Tae-Hoon; Uhm, Jae-Sun; Kim, Jong-Youn; Pak, Hui-Nam; Lee, Moon-Hyoung; Joung, Boyoung
Highlights: Particulate matter <2.5 μm in diameter (PM2.5 ) exposure is related to all-cause/cardiovascular deaths in general population. 10 μg/m 3 increments of PM2.5 are associated with 3.4 % increase of all-cause death. 10 μg/m 3 increments of PM2.5 are associated with 4.7 % increase of cardiovascular death These correlations are almost linearly associated especially above 18 μg/m 3 PM2.5 . There might be some susceptible patients who should beware of higher levels of PM2.5 . Abstract: Background: Although eastern Asian countries are exposed to high levels of air pollution, the impact of long-term exposures to fine particulate matter (PM2.5 ) air pollution on all-cause and cardiovascular mortality is not well identified. We assessed the relationship between long-term PM2.5 exposure and all-cause/cardiovascular mortalities. Methods: We included 436, 933 subjects who received national health examinations from the Korean National Health Insurance Service-based National Sample Cohort. We matched subjects' residential-address areas with hourly-measurements of PM2.5 concentration data. We estimated the risk of mortality with average PM2.5 exposure during the study period using a Cox proportional-hazards model. Results: During 1, 683, 271 person·years, all-cause and cardiovascular mortalities were observed in 6432 and 1603 subjects (382 and 95 per 100, 000 person·years, respectively). An increase in 10 μg/m 3 in PM2.5 was associated with increases in all-cause and cardiovascular mortalities by 3.4 % [2.7–4.1] and 4.7 % [3.6–5.8], respectively (each p < 0.001). PM2.5 was linearly and significantly correlated with these all-cause and cardiovascular mortalities above 18 μg/m 3 of PM2.5 ( p < 0.001), but it was not significant below 18 μg/m 3 of PM2.5 . To investigate the specific PM2.5 concentration for raising cardiovascular mortality more, we analyzed the sensitivities/specificities for different PM2.5 levels, and 18 μg/m 3 showed the highest Youden's index (sensitivity + specificity-1) with c-index of 0.85 (0.84–0.86). PM2.5 effect on all-cause mortality was more profound in subjects with previous myocardial infarction compared to the opposite population. Conclusions: In the Korean general population exposed to high-air pollution, long-term PM2.5 exposure was linearly associated with increased risk for all-cause and cardiovascular mortality, especially above 18 μg/m 3 of PM2.5 .